Tracking dynamic changes in implementation strategies over time within a hybrid type 2 trial of an electronic patient-reported oncology symptom and needs monitoring program - Smith, Justin D.; Merle, James L.; Webster, Kimberly A.; Cahue, September; Penedo, Frank J.; Garcia, Sofia F. (Frontiers in Health Services, 2022)
Background Longitudinal tracking of implementation strategies is critical in accurately reporting when and why they are used, for promoting rigor and reproducibility in implementation research, and could facilitate generalizable knowledge if similar methods are used across research projects. This article focuses on tracking dynamic changes in the use of implementation strategies over time within a hybrid type 2 effectiveness-implementation trial of an evidence-based electronic patient-reported oncology symptom assessment for cancer patient-reported outcomes in a single large healthcare system. Methods The Longitudinal Implementation Strategies Tracking System (LISTS), a timeline follow-back procedure for documenting strategy use and modifications, was applied to the multiyear study. The research team used observation, study records, and reports from implementers to complete LISTS in an electronic data entry system. Types of modifications and reasons were categorized. Determinants associated with each strategy were collected as a justification for strategy use and a potential explanation for strategy modifications. Results Thirty-four discrete implementation strategies were used and at least one strategy was used from each of the nine strategy categories from the Expert Recommendations for Implementing Change (ERIC) taxonomy. Most of the strategies were introduced, used, and continued or discontinued according to a prospective implementation plan. Relatedly, a small number of strategies were introduced, the majority unplanned, because of the changing healthcare landscape, or to address an emergent barrier. Despite changing implementation context, there were relatively few modifications to the way strategies were enacted, such as a change in the actor, action, or dose. Few differences were noted between the trial's three regional units under investigation. Conclusion This study occurred within the ambulatory oncology clinics of a large, academic medical center and was supported by the Quality team of the health system to ensure greater uptake, uniformity, and implementation within established practice change processes. The centralized nature of the implementation likely contributed to the relatively low proportion of modified strategies and the high degree of uniformity across regions. These results demonstrate the potential of LISTS in gathering the level of data needed to understand the impact of the many implementation strategies used to support adoption and delivery of a multilevel innovation. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT04014751, identifier: NCT04014751.